Analysis of Al2O3 Nano Particles and Its Deposition on Steel by Cold Spray Process. (2018) - Sammaiah, Pulla; Ashwini, V.; Suresh, A.; Sushanth, Ch.; Sudheer Kumar, N.
Abstract: The aluminium oxide material are widely used in ceramics, refractories and abrasives due to their hardness, chemical inertness, high melting point, non-volatility and resistance to oxidation and corrosion. For this study of investigation Al2 O3 nano particles were synthesized by solution combustion process and size was found to be 30 nm from X-Ray Diffraction (XRD). A thin layer of Al2 O3 nano particles on mild steel can be obtained by various means i.e., heat treatment and coating technique process by using Cold Spray process. Heat treated mild steel at 400˚C shows rough surface roughness and shows fine surface compared Base Metal. Surface roughness is higher after deposition of Al2 O3 nano particles on mild steel at 400˚C compared with Base Metal. Surface roughness is low after deposition of Al2 O3 nano particles on mild steel at 400˚ C when compared with Heat Treated sample at 400˚ C. The hardness of the base metal is low when compared with heat treated mild steel at 400˚C. When compared with base metal the coated sample at 400˚C shows high hardness because of maximum deposition of Al2 O3 nano particles on mild steel. The hardness is high after coating nano particles on mild steel at 400˚C. Coated samples are characterized by XRD, SEM and Rockwell hardness.